Exploring knowledge, attitudes, and practices toward older adults with hypertension in primary care - Chotisiri, Luckwirun (J Multidiscip Healthc, 2016)
PURPOSE: High blood pressure increases the risk of cardiovascular and kidney diseases. The purpose of this study was to explore a baseline of hypertension knowledge, attitudes, and practices among older adults with hypertension at a sub-district Health Promoting Hospital in the Pathum Thani province of Thailand. PATIENTS AND METHODS: A cross-sectional study was conducted at the outpatient clinic of the sub-district Health Promoting Hospital, one of the primary care sectors, between January and March 2015, and a total of 144 cases were recruited. All clinical parameters were collected and a structured questionnaire was used. Data were analyzed by means of descriptive statistics and chi-square tests. RESULTS: Most of the participants (74.3%) were females, and their mean age was 66.1 years. Two-thirds (66.7%) were married, unemployed/retired (67.4%), and had completed elementary education (79.2%). The screenings showed that their mean blood pressure was 136.4 (±14.4)/79.2 (±10.1) mmHg, the group’s mean body mass index was 24.9 kg/m(2) (± 3.6 kg/m(2)), and their mean waist circumference was 88.6 cm (±7.1 cm) for males and 85.7 cm (±6.8 cm) for females. In addition, their mean score of hypertension knowledge was high, and most of the participants had a neutral attitude toward hypertension; their practices in terms of dietary and exercise habits for controlling blood pressure were low in nature. CONCLUSION: This study indicated that increasing patients’ practices would be useful for promoting their healthy behaviors to achieve blood pressure control.